Pemberdayaan Keterampilan Penelitian Tindakakan Kelas Bagi Kepala Sekolah - Fakhri, Husnizar, Mukhlis, Mashuri, Ranty Maulya (Bansigom Na Publisher, 2024)
Education has a crucial role in shaping the character and skills of students, involving moral, social, and lifestyle. A great responsibility in education as a vehicle to support the holistic growth of students lies with the headmaster, the main leader in the school environment. In improving the quality of education, the headmaster is not only involved in administration but must also develop innovative strategies, such as the empowerment of classroom action research (Penelitian Tindakan Kelas, PTK). PTK proves its strategic role in improving the quality of learning and providing active opportunities for principals. The international community service program, involving various parties including school principals, the Education Office, and the Ministry of Religious Affairs, shows support for increasing public understanding of educational issues. Evaluation of service activities becomes important to measure the achievement of goals, positive impact, community involvement, continuity of activities, and direct feedback. The evaluation results support the positive contribution of service activities, creating expectations of positive change in the world of education through joint efforts